Comparative exergy analysis of selected fuels for internal combustion engines / Mohd Faizal Fauzan - Mohd Faizal, Fauzan (2011)
This dissertation examines the detailed thermodynamics models for naturally aspirated gasoline and alternative fuelled to spark ignition internal combustion engines on the basis of ideal Otto cycle. A comparative study based on the first and second laws of thermodynamics are discussed here. The key parameters for analysis are considered as mean effective pressure (MEP), power, torque, exergetic efficiency, second law efficiency, and irreversibility. Air standard assumptions were taken consideration for the analyses. MEP, power output and torque for all alternative fuelled engines, are higher compared to that of a gasoline engine. Exergy due to heat and work are also discussed here. For heat exergy, only hydrogen exceeds gasoline while other alternative fuels have lower heat exergy than gasoline. But work (mechanical) exergy for all the alternative fuelled engines are higher than the gasoline engine. The Irreversibility or losses for the alternative fuelled engines are significantly lower than a gasoline engine. Alternative fuel engines have lower specific fuel consumption than the gasoline engine. Hence the 1st law and second law efficiency of the alternative fuelled engines are higher compared to that of gasoline. This is also due to having a high compression ratio associated with alternative fuelled internal combustion engine. Exergy heat transfer of alternative fuelled internal combustion engine is higher due to having high heat generation during combustion.